Interfacial two-dimensional oxide enhances photocatalytic activity of graphene/titania via electronic structure modification. (February 2020) - De Angelis, Dario; Presel, Francesco; Jabeen, Naila; Bignardi, Luca; Lizzit, Daniel; Lacovig, Paolo; Lizzit, Silvano; Montini, Tiziano; Fornasiero, Paolo; Alfè, Dario; Baraldi, Alessandro
Abstract: The photocatalytic activity of titania nanoparticles deposited on epitaxial graphene is proven to be significantly affected by the substrate on which graphene is supported. In particular, it has been revealed that the addition of a two-dimensional TiO1.5 layer sandwiched between graphene and the supporting metal induces a p-doping of graphene itself and a consistent shift in the Ti d states. These modifications in the electronic structure are compatible with the reduction of the probability of charge carrier recombination and enhance the photocatalytic activity of the heterostructure. This is indicative of the capital role played by the interfacial thin oxide films in fine-tuning the properties of heterostructures based on graphene and pave the way to new combinations of graphene/oxides for photocatalysis-oriented applications. Graphical abstract: Image 1